Rehabilitation of severely mutilated teeth under general anesthesia in an emotionally immature child - Navit S; Katiyar A; Samadi F; Jaiswal J (Wolters Kluwer Medknow Publications, 2010)
Dental caries is the single most common chronic childhood disease. In rampant caries, there is early pulp involvement and gross destruction of the maxillary anterior teeth as well as posterior teeth. This leads to decreased masticatory efficiency, difficulty in speech, compromised esthetics, development of abnormal tongue habits and subsequent malocclusion and psychological problems. The restoration of severely decayed primary incisors is often a procedure that presents a special challenge to dentists, particularly in an uncooperative child. This case report documents the restoration of severely mutilated deciduous teeth in an emotionally immature patient under general anesthesia.